PENGEMBANGAN NILAI-NILAI AGAMA PADA TAMAN PENDIDIKAN ANAK SHALEH (TAPAS) SURABAYA - Yani, Muhamad Turhan (Pendidikan Dasar, 2009)
Abstract : In the religion (Islam) concept, children in the early age/kindergarten should have been trained to develop the positive aspect in order in the mature age are used to do the positive things and finally shaped the good personality. The purpose of this research is to describe and analyze the applied method by teachers of Anak Shaleh Education Kindergarten (TAPAS) in development of religious values on their pupil and also concrete examples. Data collection was done through observation and interview, the being critically analyzed, lending the Arief Furqans term is reflective thinking. The research result is the TAPAS teachers denoted the variation method in developing the religious valued to the students and also give the concrete examples, although there are something in the child development psychology review was less appropriate done, such as the teachers often give material to be memorized for example, short letters, prayers, even include in the material of exams.